A comparison of strength and power characteristics between power lifters, olympic lifters, and sprinters - McBride, J. M.; Triplett-McBride, T.; Davie, A.; Newton, R. U. (The Journal of Strength and Conditioning Research, 1999)
The purpose of this investigation was to determine the effect of involvement in power lifting, Olympic lifting, and sprinting on strength and power characteristics in the squat movement. A standard one repetition maximum squat test, jump squat tests, and vertical jumps with various loads were performed. The power lifters (PL, n = 8), Olympic lifters (OL, n = 6), and sprinters (S, n = 6) were significantly stronger than the controls (C, n = 8) (p 0 .05). In addition, the OL group was significantly stronger than the S group. The OL group produced significantly higher peak forces, power outputs, velocities, and jump heights in comparison to the PL and C groups for jump trials at various loads. The S group produced higher peak velocities and jump heights in comparison to the PL and C groups for jump trials at various loads. The PL group was significantly higher in peak force and peak power for jump trials at various loads in comparison to the C group. The data indicates that strength and power characteristics are specific to each group and are most likely influenced by the various training protocols utilized.